Certificate in park guide training course - Chan, Margaret (UiTM Sarawak, 2020)
Universiti Teknologi MARA conducted two Certificate in Park Guide Training Courses to prepare potential or practising unlicensed park guides to obtain the certificate as a qualification to obtain Park Guide License in the second half of 2019. Sarawak Forestry Corporation Sdn Bhd is the training provider where UiTM is the training consultant under section 8 of the National Parks and Nature Reserves Ordinance 1998 and its regulation 1999. The duration of the program is 13-16 days depending of the number of participants.